GUGUR DAUN TANAMAN KARET AKIBAT PENYAKIT PHYTOPHTHORA SPP. DI PERKEBUNAN KARET JEMBER, JAWA TIMUR - Intan Berlian; Budi Setyawan (Warta Perkaretan, 2017)
Renteng and Banjarsari field is a part of PT. Perkebunan Nusantara XII, located in Jember with major commodity of rubber plant. Since December 2013, leaf fall occurred in Renteng field Afdeling Sidomulyo (year of planting 1996) and Banjarsari field Afdeling Karang Nangka (year of planting 1993). The study was conducted in January to March 2014. Identification of the leaf fall was used macroscopic, microscopic and continued with Koch's postulates. The results showed that yellowing of leaf that's accompanied by leaf fall in Afdeling Sidomulyo (year of planting 1996) and Afdeling Karang Nangka (year of planting 1993) caused pathogen Phytophthora spp. This study has been proved that Phytophthora spp. causes the leaf fall in Indonesia after the last report in 1977.